Peptic ulcer disease in school children aged 2-11 years in Southeast Nigeria - Umegbolu, Emmanuel I. (International Journal of Research in Medical Sciences, 2022)
Background: A peptic ulcer is a sore on the inner lining of the stomach or duodenum, caused mainly by non-steroidal anti-inflammatory drugs and Helicobacter pylori infection. In childhood, peptic ulcer disease (PUD) is an uncommon disease, with an estimated frequency of 1 case in 2, 500 hospital admissions in the United States. Data for developing countries, including Nigeria, are scarce, although peptic ulceration is being increasingly recognized in children in the developing world now. For this reason, this study was designed to investigate PUD in school children in Southeast Nigeria. Methods: 264 children, aged 2-11 years, who attended Cottage Hospital Inyi in 2020 with complaints of abdominal pain were investigated for PUD with stool antigen test. Data collected for a period of one year were analysed as proportions and Chi square, using MaxStat (version 3.60) statistical software. P≤0.05 was considered significant. Results: The prevalence of PUD was 16%; 8.3% in females and 7.6% in males. In the 2-6 years age group prevalence was 7%, while in the 7-11 years age group it was 9%. Association between sex and prevalence of PUD was not significant (p=0.62), but very significant for that with age (p=0.0003). Conclusions: Prevalence of PUD was 16%. This increased with age (7% in the 2-6 years age group and 9% in the 7-11 years group). To address the rising prevalence of PUD in these children, there is need to monitor their feeding habits in school, besides teaching them the importance of personal hygiene.